2023
DOI: 10.1021/acsenergylett.3c00917
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Lithium-Ion Conductive Interphase with Gradient Desolvation Effects for Fast-Charging Lithium Metal Batteries

Abstract: Efficient desolvation and fast lithium ion (Li + ) transport are key factors for fast-charging Li metal batteries (LMBs). Here, we report a self-assembled interphase (SAI) with ordered Li + transport pathways to enable high Li + conductivity and fast Li + desolvation for fastcharging LMBs. A self-assembled structure originating from the intermolecular π−π stacking endows SAI with ordered Li + transport pathways. The regular molecular stacking and a gradient distribution of functional groups of SAI contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…ToF-SIMS measurement is also carried out to probe the components of SEI; it can be seen from Figure d and e that B–O species are obviously observed on the lithium anode recovered from the PLDPB-based cell, which further indicates that the decomposition of PLDPB contributes to the SEI formation. , The B–O species is richer in the inner layer of the SEI, as demonstrated by the B 1s spectra. It is reported that the benzene-based organic moiety with planar backbone conformation and π–π interaction might be beneficial for the formation of flat and compact SEI layers and simultaneously improve the toughness and strength of SEI and thus suppress growth of lithium dendrites. ,, More importantly, a close inspection of C 1s and O 1s signals in Figure c reveals that the peaks of organic species, especially the O–C(O)–O peak, drop sharply after 200 s of sputtering, which demonstrates that the formed inner SEI might inhibit the parasitic reactions, and many fewer organic carbonate plasticizers (i.e., EC/DEC solvents) decompose in the inner part of SEI in the PLDPB-based electrolyte. On the contrary, for the LiTFSI-based cell, the O–C(O)–O peak remains almost the same without obvious attenuation during the whole XPS sputtering (see the O 1s spectra in Figure S13), indicating organic compounds might be enriched from the outer to the inner layer due to the continuous consumption and decomposition of plasticizers .…”
Section: Results and Discussionmentioning
confidence: 94%
“…ToF-SIMS measurement is also carried out to probe the components of SEI; it can be seen from Figure d and e that B–O species are obviously observed on the lithium anode recovered from the PLDPB-based cell, which further indicates that the decomposition of PLDPB contributes to the SEI formation. , The B–O species is richer in the inner layer of the SEI, as demonstrated by the B 1s spectra. It is reported that the benzene-based organic moiety with planar backbone conformation and π–π interaction might be beneficial for the formation of flat and compact SEI layers and simultaneously improve the toughness and strength of SEI and thus suppress growth of lithium dendrites. ,, More importantly, a close inspection of C 1s and O 1s signals in Figure c reveals that the peaks of organic species, especially the O–C(O)–O peak, drop sharply after 200 s of sputtering, which demonstrates that the formed inner SEI might inhibit the parasitic reactions, and many fewer organic carbonate plasticizers (i.e., EC/DEC solvents) decompose in the inner part of SEI in the PLDPB-based electrolyte. On the contrary, for the LiTFSI-based cell, the O–C(O)–O peak remains almost the same without obvious attenuation during the whole XPS sputtering (see the O 1s spectra in Figure S13), indicating organic compounds might be enriched from the outer to the inner layer due to the continuous consumption and decomposition of plasticizers .…”
Section: Results and Discussionmentioning
confidence: 94%
“…It is evident that the PVA-CN polymer effectively enhances the stability of the electrode-electrolyte interface and restrains uncontrolled growth of Li dendritic, which is attributed to the abundance of À OH groups in the the PVA-CN polymer. [27,28] To further understand the underlying mechanism of how the PVA-CN in BPPL stabilizes Li with electrolyte, we investigated the desolvation process of solvated Li + , as reported in the previous study. [7] It's widely acknowledged that the C=O group of EC binds to Li + , and the typical solvation number for the first solvation shell is n = 4, denoted as Li(EC) 4…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Li deposition within PVA‐CN+LE demonstrated a dendrite‐free and denser layer even after 16 mins at 5 mA cm −2 (Figure 3b). It is evident that the PVA‐CN polymer effectively enhances the stability of the electrode‐electrolyte interface and restrains uncontrolled growth of Li dendritic, which is attributed to the abundance of −OH groups in the the PVA‐CN polymer [27,28] …”
Section: Resultsmentioning
confidence: 99%
“…[ 39 ] The confinement effect holds the promise of facilitating the decomposition of solvated metal ions by directly regulating the physical and chemical properties of the electrolyte, ultimately inhibiting side reactions. [ 40 ] Compared to the concentrated electrolyte, the confinement effect effectively reduces the reactivity of free solvent molecules and induces desolvation by directly modulating the chemical environment of the liquid electrolyte. This approach enables the production of electrolytes with enhanced electrochemical performance while maintaining the same salt concentration, making it a promising alternative modification for liquid electrolytes.…”
Section: Harnessing Confinement Effects In Rechargeable Batteriesmentioning
confidence: 99%